Designing the future of bond markets: Reducing transaction costs through tokenization - David Cisar; Benjamin Schellinger; Jens-Christian Stoetzer; Nils Urbach; Florian Lennart Weiß; Vincent Gramlich; Tobias Guggenberger (Electronic Markets, 2025)
Corporate bonds are an attractive option for corporate financing. However, current bond markets face many challenges and inefficiencies, resulting in high transaction costs (TAC). In recent years, technological advancements like blockchain technology have enabled the possibility of reducing TAC in bond markets. Even though practice experiments with such solutions, academic literature lacks generic design knowledge under the TAC lens to design blockchain-based bonds. Thus, our research follows the design science research (DSR) paradigm to design and develop a bond prototype using the Ethereum blockchain protocol. Our results highlight the capability of blockchain-based bond markets to reduce TAC in the three dimensions of asset specificity, uncertainty, and transaction frequency. Further, our research provides design principles to contribute to both practice and the academic discourse on developing blockchain-based bond markets with reduced TAC.
Keywords: M15; G14; D23; 620; Bonds; Design science research; Transaction cost theory; Blockchain